Pengaruh Opini Audit, Umur Perusahaan, Profitabilitas, Dan Pergantian Auditor Terhadap Audit Report Lag Pada Perusahaan Manufaktur Yang Terdapat Di Bursa Efek Indonesia (BEI) Pada Tahun 2017 – 2019 - Valentina Lorensa br Sitompul; Firma Kristin Agustina Simanjuntak; Wenny Anggeria Ginting (Journal of Economic, Bussines and Accounting (COSTING), 2021)
The purpose of this discussion is to review the related audit opinion, company age, profitability, as well as the change of auditors in the manufacturing industry listed on the Indonesia Stock Exchange for the period 2017-2019. Researchers use quantitative research methods, meaning the data is obtained in www.idx.co.id The population of 182 issuers, while the sampling technique is purposive sampling, so the number of samples is 65 issuers with the period 2017-2019. The Hypothesis test used is logistic regression. The result is partially significant value of audit opinion 0.999 > 0.05, company age 0.008 < 0.05, profitability 0.554 > 0.05, auditor turnover 0.612 > 0.05, simultaneously significant value obtained by 0.00 < 0.05. From these results, it was concluded that audit opinions, profitability, and auditor turnover do not influence audit report lag. Meanwhile, the age of the company has an association over audit report lag, and simultaneously there is an influence between audit opinions, the age of the company, profitability, and the change of auditors on audit report lag. Keywords : Audit opinion; company age; profitability; auditor turnover; audit report lag.